If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11n + 6 = n + -44 Reorder the terms: 6 + 11n = n + -44 Reorder the terms: 6 + 11n = -44 + n Solving 6 + 11n = -44 + n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-1n' to each side of the equation. 6 + 11n + -1n = -44 + n + -1n Combine like terms: 11n + -1n = 10n 6 + 10n = -44 + n + -1n Combine like terms: n + -1n = 0 6 + 10n = -44 + 0 6 + 10n = -44 Add '-6' to each side of the equation. 6 + -6 + 10n = -44 + -6 Combine like terms: 6 + -6 = 0 0 + 10n = -44 + -6 10n = -44 + -6 Combine like terms: -44 + -6 = -50 10n = -50 Divide each side by '10'. n = -5 Simplifying n = -5
| 4-3.2=14 | | -35=b-34 | | 5w-3=67 | | 5(2x-2)=4-2c | | 3v-8v=-14-3v | | 3v-8v=-14-4v | | 4a+4b-ab=8 | | 3(x-5)+9=-24 | | x+7=14+8x | | 8t-3(4t+2)=16 | | 12/3x=5/6 | | 1.8=4(x+5) | | 5r+5=40 | | -6x-40=4(-4x+5) | | 3+8x-7x=7-x | | 5x-3+5=27 | | 4y/9-y/6=1/2 | | 4(6x-5)=6(4x+5) | | 12/3x=6/5 | | 5x-3+5-3x=-18 | | r+10=16 | | 6n-5n=-6n+3n | | 5x-3x-2=2(x-7) | | x+1/20=4000 | | 6n-5n=-6n+n | | 2x*4-x+7+4x-8-5x^2+2+3x= | | 2/3x-1/3=32/3 | | 2/3x-12=10 | | 30-75=10z-4 | | 9y-7-5y+6=0 | | 6+2(3y-2)=4(1+y) | | d-8=10 |